Pengaruh penambahan Ion Logam Natrium, Kalium, Magnesium, Kalsium pada biokonversi tepung jagung (Zea Mays L.) oleh Ragi Endomycopsis Fibuligera menjadi Senyawa Prebiotik - Astuti Amin; asnita asnita (Jurnal Kimia Fullerene, 2020)
In this study made prebiotic from bioconversion of corn flour (Zea mays L.) by yeast Endomycopsis fibuligera as an alternative substitute for antibiotics. In this study, the addition of Na+, K+, Ca2+, and Mg2+ ions aimed to determine the optimum type and concentration of metal in prebiotic and testing the effect of prebiotic compounds produced on broiler weight gain. The analysis carried out included: reducing sugars, α-amylase and glucoamylase enzyme activity, protein content and cell biomass. To determine the existence of a significant effect, the analysis was carried out on broiler body weight given prebiotic compounds which were added to optimum metal ions and which were given prebiotic compounds without the addition of metal ions. The results showed that the addition of optimum metal ions was obtained on Ca2+ ions with a concentration of 0.25%, where the reducing sugar content of 0.600 mg / mL, the activity of the enzyme α-amylase and glucoamylase 0.519 and 0.287 units / mL, protein content 2.724 mg / mL, cell biomass 10.8933 mg / mL, from observations and statistical tests carried out by giving prebotic compounds by adding metal ions and giving prebiotic compounds without adding metal ions influence broiler weight gain with an average weight difference of 261 grams or 15% on day 30.